A Study of Gender, Masculinities and Reintegration of Former Combatants in Rwanda : Results from the International Men and Gender Equality Survey - World Bank (Washington, DC, 2014)
The International Men and Gender Equality Survey (IMAGES) created and coordinated by Promun¬do and the International Center for Research on Women (ICRW) is one of the most comprehen¬sive studies ever on men s practices and attitudes as they relate to gender norms, attitudes toward gen¬der equality policies, household dynamics including caregiving and men s involvement as fathers, inti¬mate partner violence, health and economic stress. As of 2013, it had been carried out in 10 countries with additional partner studies in Asia inspired in part by IMAGES.